PERBANDINGAN PEREKONOMIAN DARI MASA SOEKARNO HINGGA SUSILO BAMBANG YUDHOYONO (1945 - 2009) - Hakim, Abdul; Giovani, Guswildan (Faculty of Economics and Business, University of Muhammadiyah Malang, 2012)
This research to analyzes Indonesia's economy in various presidency, that since Indonesia's independence in 1945 until 2009. This study used qualitative research methods-historical, and found that each leadership has their stated objectives. In Suharto, began development with a clearer direction. But the factor of corruption, collusion and nepotism makes the New Order fall. Habibie did re-alignment in the economic, social and political. Gus Dur emphasizes building relationships with foreign countries in order to build the national economy. Megawati succeeded in lowering inflation and interest rates, and increase economic growth and menguatlan rupiah. Susilo Bambang Yudhoyono succeeded in improving the economy in general, inflation mengendaikan, growing domestic aggregate demand, and reduce imports